Self-healing of Poly(2-hydroxyethyl methacrylate) hydrogel through molecular diffusion - N.A. Sirajuddin; M.S. Md Jamil (Universiti Kebangsaan Malaysia, 2015)
Synthetic materials that are capable of healing upon damage are being developed at a rapid pace because of their many potential applications. Here, new healing chemically cross-linked hydrogel of poly(2-hydroxyethyl methacrylate) (pHEMA) was prepared. The healing hydrogel was achieved by heating above its glass transition (Tg). The intermolecular diffusion of dangling chain and the chain slippage led to healing of the gel. The peaks in attenuated total reflectance (ATR) confirmed that hydrogel was formed while rheological studies had determined the minimum for healing temperature is 48.5oC. The results showed that ratio stress of the healable hydrogel can reach until 92 and 91% of first and second healing cycle, respectively. The morphology of the sample was carried out to evaluate the self-property of hydrogel.